PENGARUH BUDAYA KERJA TERHADAP PRODUKTIVITAS DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI PT. AKUR PRATAMA (YOGYA RIAU JUNCTION) - Subarnas, Alya Nabiila Febryanti; Recky, Recky; Aziz, Dadan Abdul (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
This study aims to analyze the influence of Work Culture on Productivity with Work Motivation as a mediating variable at PT. Akur Pratama, Yogya Riau Junction Bandung branch. The research employs a quantitative approach based on positivism, with all 95 employees serving as the research sample through a census technique. Data collection was carried out using research instruments, and the data were analyzed statistically to test the formulated hypotheses. The results indicate that Work Culture has a significant positive effect on Work Motivation, highlighting the role of organizational cultural elements, such as values and work norms, in fostering employee motivation. Additionally, Work Culture also positively influences Productivity, although its impact is not as strong as on Work Motivation. Work Motivation was found to have a substantial and significant impact on Productivity, both directly and as a mediating factor. The indirect relationship between Work Culture and Productivity through Work Motivation suggests that employee motivation plays a critical role in enhancing the influence of work culture on productivity. Keywords: